Effects of habitat fragmentation on population structure and long-distance gene flow in an endangered marsupial: The woylie - Pacioni, Carlo; Wayne, A.; Spencer, P. (2011)
A deep understanding of population structures and of the relationships among populations is fundamental to guarantee adequate management of endangered species. We used a molecular approach (12 microsatellite loci and mitochondrial DNA) to investigate these aspects in the woylie or brush-tailed bettong Bettongia penicillata ogilbyi. Four distinct indigenous populations were identified in this study (i.e. Dryandra woodland and Tutanning nature reserve in the wheatbelt region and two discrete populations in the Upper Warren in the south-west forests of Western Australia). Additionally, previously undisclosed modern and historical connections between these units became evident, such as the historical connection between populations at 150 km distance (Dryandra and Upper Warren) and the contemporary gene flow between the two populations in Upper Warren (up to 60 km). Genetic attributes of the four populations were analysed and the evidence of unique genetic material in each of these populations indicated that conservation effort should aim towards the preservation of all these units. Additionally, the lower genetic diversity of the woylie population in Tutanning nature reserve prompted the need for the investigation of factors that are limiting the demographic growth of this population. This study enhances not only our knowledge about the ecology of woylies but also the genetic consequences of habitat fragmentation and reiterates the strength and pertinence of molecular techniques in similar investigations. © 2010 The Authors.